2016
DOI: 10.3389/fnbeh.2016.00138
|View full text |Cite
|
Sign up to set email alerts
|

Combining Real-Time fMRI Neurofeedback Training of the DLPFC with N-Back Practice Results in Neuroplastic Effects Confined to the Neurofeedback Target Region

Abstract: In traditional fMRI, individuals respond to exogenous stimuli and are naïve to the effects of the stimuli on their neural activity patterns. Changes arising in the fMRI signal are analyzed post-hoc to elucidate the spatial and temporal activation of brain regions associated with the tasks performed. The advent of real-time fMRI has enabled a new method to systematically alter brain activity across space and time using neurofeedback training (NFT), providing a new tool to study internally-driven processes such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…The mental-rehearsal control condition can be implemented both inside (57,59,60,(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80) and outside the MRI scanner (e.g., 41,81,[82][83][84]. The latter option is much easier to realize and considerably decreases associated (personnel and scanning) costs.…”
Section: Mental-rehearsal Controlmentioning
confidence: 99%
“…The mental-rehearsal control condition can be implemented both inside (57,59,60,(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80) and outside the MRI scanner (e.g., 41,81,[82][83][84]. The latter option is much easier to realize and considerably decreases associated (personnel and scanning) costs.…”
Section: Mental-rehearsal Controlmentioning
confidence: 99%
“…Several studies successfully demonstrated that the participants using real-time feedback in fMRI-BCI were able to perform voluntary self-regulation on a focused brain region, see details in Ruiz et al (2014) and Sorger et al (2018) . The applications of real-time neuro-feedback in fMRI-BCI for healthy subjects include the voluntary self-regulation of motor areas ( Yoo and Jolesz, 2002 ; Yoo et al, 2004 , 2008 ; Berman et al, 2012 ; Johnson et al, 2012 ), sensory areas ( Scharnowski et al, 2012 ; Robineau et al, 2014 ; Auer et al, 2015 ), auditory cortex ( Yoo et al, 2006 ), language areas ( Rota et al, 2009 ), emotion areas ( Weiskopf et al, 2003 ; Caria et al, 2007 , 2010 ; Zotev et al, 2011 ), and working memory areas ( Zhang et al, 2013 ; Sherwood et al, 2016 ). In the case of patients, the real-time neuro-feedback helps to remediate the pathological brain activation associated with different disorders including neurological disorders ( Subramanian et al, 2011 ; Sitaram et al, 2012 ; Guan et al, 2015 ) and psychiatric disorders ( Ruiz et al, 2013 ; Hartwell et al, 2016 ; Kirsch et al, 2016 ; Zotev et al, 2016 ).…”
Section: Role Of the Initial Dip In Bcimentioning
confidence: 99%
“…(The full list of 95 contributing regions is included as Supplementary Table 1.) This analysis goes beyond previous studies that have determined that DLPFC is especially active during n-back tasks (Evangelista et al, 2021;Kumar et al, 2017;Sherwood et al, 2016;Woodcock et al, 2018) and studies that have characterized DLPFC connectivity (Cole et al, 2012;Panikratova et al, 2020;Reineberg & Banich, 2016), revealing likely direct causal mechanisms contributing to DLPFC's involvement in n-back task cognitive processes. As mentioned before, this single-causal-step activity flow model represents a starting point for a more comprehensive multiple-causal-step neurocognitive explanation of working memory.…”
Section: Directed Activity Flow Models Improve Mechanistic Insight Into Task Condition Selectivitymentioning
confidence: 62%